The effects of altitude training are mediated primarily by acclimatization, rather than by hypoxic exercise - Levine, B. D.; Stray-Gundersen, J. (Advances in Experimental Medicine and Biology, 2001)
For training at altitude to be effective, it must provide some advantage above and beyond similar training at sea level. This advantage could be provided by: 1) acclimatization to altitude which improves oxygen transport and/or utilization; 2) hypoxic exercise which "intensifies" the training stimulus; or 3) some combination of both. Controlled studies of "typical" altitude training, involving both altitude acclimatization and hypoxic exercise have never been shown to improve sea level performance. This failure has been attributed to reduced training loads at altitude. One approach developed by Levine and Stray-Gundersen, called "living high-training low" has been shown to improve sea level performance over events lasting 8-20 minutes. This strategy combines altitude acclimatization (2,500 m) with low altitude training to get the optimal effect. The opposite strategy, "living low-training high" is proposed by Dr. Hoppeler in this debate. In defense of the primacy of the altitude acclimatization effect, data will be presented to support the following: 1). Living high-training low clearly improves performance in athletes of all abilities; 2). The mechanism of this improvement is primarily an increase in erythropoietin leading to increased red cell mass, VO2max, and running performance; 3). Rather than intensifying the training stimulus, training at altitude leads to the opposite effect--reduced speeds, reduced power output, reduced oxygen flux--and, following the principal of symmorphosis, is not likely to provide any advantage for a well trained athlete; 4). At the moderate altitudes used by most athletes, resting oxygen delivery to skeletal muscle is well preserved, arguing against any detrimental effect on "protein synthesis"; 5). It is possible however, that at significantly higher altitudes, acclimatization leads to appetite suppression, inhibition of protein synthesis, muscle wasting, excessive ventilatory work, and metabolic compensation that is NOT advantageous for a competitive athlete.